Prices in India : Prices in India : An Analysis (Globalisation and Free Trade Impact) - Anwar, Khalid; Bhattacharya, Jaydeep (Journal of Commerce and Trade, 2008)
Globalization, it is often argued, would - by promoting free trade among nations and lifting all barriers to the entry of goods, services, technology and investing - create competitive conditions within an economy which on the one hand would force producers to strive for operational efficiency and, on the other hand would benefit the consumers through lower prices of product and improved quality. When India has completed sixteen years of its journey through the reform process, a question naturally arises; to what extent the above expectation of Indian consumers regarding prices has actually been fulfilled? To know this, the present paper proposes to examine the prices trends - both wholesale and consumers prices - in the post 1991 period and compares the same with the pre-reform trends. The analysis reveals that globalization polices by and large have failed to fulfil the expectation of the Indian consumers.